Retrogradation of autoclaved corn starches: Effect of water content on the resistant starch formation and structure. (November 2020) - Soler, Adrian; Velazquez, Gonzalo; Velazquez-Castillo, Rodrigo; Morales-Sanchez, Eduardo; Osorio-Diaz, Perla; Mendez-Montealvo, Guadalupe
Abstract: In this study, the resistant starch (RS) formation, crystallinity, and double helical order of autoclaved (120 °C) normal (ANS) and high amylose (AHS) corn starches retrograded at ~4–26% of water content were investigated. ANS and AHS retrograded at ~25–26% of water content were more crystalline (~35–40%) and formed by more close-packed double helices (R1000/1022  cm −1  = 1.145–1.290). The highest content of RS (38.8%) was found in AHS retrograded at 25.52% of water content meanwhile in ANS, the maximum content of RS was 6.6% at 21.60% of water content despite its structural order was increased with the increase of water content. The recrystallization of amylopectin interfered with the formation of homogeneous crystalline structures of amylose preventing the formation of retrograded RS in ANS, while in AHS, a relationship between structure and RS formation was observed, suggesting that the close-packed double helices and the proportion of homogeneous amylose crystallites increased the resistance to enzymatic digestion. Graphical abstract: Image 1 Highlights: Retrogradation of autoclaved corn starches at ~4–26% water content was investigated. ~26% of water content improved the structural order in autoclaved corn starches. 25.52% of water content yielded a resistant starch content of 38.8%. Homogeneous amylose crystallites were related to the resistant starch formation. Amylopectin recrystallization inhibited the resistant starch formation.